Leaks, Hacks, and Scandals: Arab Culture in the Digital Age, written by Tarek El-Ariss. - Limbrick, Peter (Journal of Arabic Literature, 2021)
El-Ariss organizes the chapter around the case of Wael Abbas, the Egyptian activist-blogger who was one of the first to post videos online of Egyptian police brutality. In the latter three chapters, El-Ariss focuses more on the reading of particular texts, which include Twitter feeds, novels, and the discourse around and about them.